Improvising the Design of Optical Geometric Experiment Apparatus for Pre-University Physic Course - Abdul Yatim, Adzra Ibrahim; Bareduan, Salleh Ahmad; Abdul Karim, Mohd Sharin; CHOO, LEY IN; Mohamad Dewa, Abdul Ghani (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Several difficulties have arisen for pre-university physics students using the retort stand as a laboratory apparatus for optical geometric experiments. The school staffs introduced the G-Optic Slider in 2020 to improve students’ understanding and address the need for more conventional setups in optical geometric studies. The G-Optic Slider uses a fixed pin mechanism, a ruler, and recycled plastic pipettes to handle visualization and pin location. The present analysis highlights the G-Optic Slider’s design limitations and emphasizes further improvement. The research goals include finding flaws, rebuilding the apparatus, and building a prototype, emphasizing convex lens experiments for Form Six Physics Courses. The research incorporates sustainability components via eco-friendly materials and fosters cooperation across educational institutions to improve student involvement, comprehension, and overall grades. Three concepts of improved G-Optic Slider were studied, and the selected proposal was designed using SolidWorks software. The suggested design has a pinion, rack mechanism, and PLA as the material. The drawing was then transferred to CuraMaker software for the 3D printing manufacturing process. Additional recommendations include a movable lens holder, simple mechanism , durable materials like polypropylene, and practical 3D printing for low-cost manufacturing. Finally, this project effectively overcomes shortcomings in the current Optical Geometric Experiment Apparatus and provides a better design that improves physics students’ pre-university learning experience. The study emphasizes the continuous need for research to improve and optimize instrument designs, laying the foundation for future advancements.